The effect of the P.M.L strategy on the achievement of physical geography among fifth grade female students - Asst.Lact. Raghad Hamedan Abd Rustamawy (Journal of College of Education, 2024)
The current research aims to determine the impact of the P.M.L strategy on the acquisition of geography subject knowledge among fifth-grade female students. To achieve this goal, the researcher formulates the following null hypothesis: There is no statistically significant difference at the (0.05) level between the average grades of the experimental group students studying physical geography according to the P.M.L strategy and the average grades of the control group students studying the same subject using the traditional method in the post-test. To achieve this, the researcher adopts the experimental approach with a post-test design, deliberately choosing Um Al-Qura Girls' Preparatory School. The research sample consisted of 64 fifth-grade literary female students, with 32 students in each group. For the experiment, Group A was randomly selected to represent the control group, while Group B represented the experimental group. Equivalence was ensured between the two research groups in variables such as intelligence, chronological age (measured in months), and previous year's geography grades. The researcher formulate 92 behavioral objectives distributed across Bloom's taxonomy levels in the cognitive domain (knowledge, comprehension, application) for the content of the first three chapters of the physical geography book. The researcher employed statistical methods (independent samples t-test) and appropriate statistical procedures in the research process. The results of the research showed that the experimental group students studying physical geography according to the P.M.L strategy outperformed the control group students studying the same subject using the traditional method in the post-test.
Keywords: Impact, P.M.L strategy, geography, fifth-grade female students.